Evaluation of the offensive behavior of elite soccer teams - Papadimitriou, K.; Aggeloussis, N.; Derri, V.; Michalopoulou, M.; Papas, M. (Perceptual and Motor Skills, 2001)
The purpose of the present study was to evaluate the offensive behavior of the four elite teams (France, Brazil, Croatia, and Holland) using data from the semifinals of the 18th World Soccer Championship in France in 1998. 28 videotaped soccer games were observed, 7 for each team. The protocol contained the following parameters of evaluation: (a) successful pass in the defensive and middle area, (b) unsuccessful pass in the defensive and middle area, (c) attempt on goal in the offensive area, and (d) cross and follow-up action. A multivariate analysis of variance showed the teams' plan was significantly different only in playing the ball back to the goalkeeper. This last action, used more often by Holland than by the other teams, indicated its restrained offensive behavior, which may be one of the reasons for its defeat in some games.